Synthesis and characterization of monolithic CVD-SiC tubes. Issue 8 (July 2016) - Drieux, Patxi; Chollon, Georges; Jacques, Sylvain; Couégnat, Guillaume; Jouannigot, Stéphane; Weisbecker, Patrick
Abstract: The high open porosity of SiC/SiC composites is problematic for uses in advanced thermal or confinement systems. A strong and gas-tight SiC sheath would helpfully complete the composite structure. The aim of this work was to prepare and characterize long, free standing and high strength SiC tubes obtained through a rapid near net shape manufacturing process. The tubes were produced by continuous chemical vapor deposition (CVD) at atmospheric pressure using CH3 SiHCl2 /C3 H6 /H2 mixtures. The composition, morphology and microstructure of the CVD-SiC tubes were analyzed in details. The Si/C ratio and crystalline state through wall thickness are related to the progress of gas phase reactions during continuous deposition. The silicon excess in the CVD-SiC coating can be reduced by preheating gases and adding C3 H6 . C-ring specimens cut from the tubes were submitted to compressive tests at room and high temperature to assess their failure properties and thermomechanical behavior.